Selected fundamentals of catalysis and electrocatalysis in energy conversion reactions—A tutorial - Roduner, Emil (Catalysis today, 2018)
•Upscaling power density requires downscaling transport distances to minimize loss.•Energy intensive reactions are driven by electricity instead of heat.•Anode-cathode separation may prevent the back-reaction of high energy products.•Electrode surfaces are akin to surfaces of conventional heterogeneous catalysts.•Catalysis/electrocatalysis research is empirical, based on experience and intuition. [Display omitted] Electrochemical devices for energy conversion and storage applications have little in common with conventional electrochemistry. A significant advantage is the conversion of chemical into electrical energy and vice-versa, minimizing the amount of waste heat. Upscaling power density to values reaching up to 1Wcm−2 at current densities exceeding 1Acm−2 goes along with downscaling transport distances of reaction partners inside and between electrodes. Substrates undergo structure- and element-specific interactions with electrode surfaces which are therefore not only interfaces for the exchange of electrons, rather they should be regarded as specific catalytic surfaces which together with the applied electrical bias potential determine the spectrum of available products. An understanding of these interactions is still in its infancy for many of the relevant systems, and therefore the developments are largely empirical and driven by intuition, supported by quantum-chemical calculations and spectroscopic methods. The manuscript is of tutorial nature and addresses the differences between electrocatalysis in energy conversion reactions and conventional electrochemistry, and it reveals what catalytic transformations at electrode surfaces have in common with traditional heterogeneous catalysis.